Core-shell structured catalysts, methods of making and using the same, and methods of glycerol synthesis of 1,3-propanediol
Patent Information
- Application Number
- CN202510557532.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的是为了克服现有技术存在的合成1,3-丙二醇的催化剂在水热反应中,活性低和稳定性差的问题,提供一种核壳结构催化剂及其制备方法与应用、甘油合成1,3-丙二醇的方法,该催化剂具有负载W的TiO2纳米薄膜外壳,能够在增强氢溢流,同时稳定夹层中Pt纳米颗粒,使催化剂具有较高的催化反应活性
[0023](1)本发明中,所述催化剂具有核壳结构,外壳的含W的TiO2纳米薄膜对夹层的Pt纳米颗粒起到固定作用,具有更加稳定的结构,避免活性组分的聚集和流失,外壳负载的W同时能够提供更多的催化活性位点,所述催化剂具有高活性和高水热稳定性;
Smart Images

Figure CN122999191A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalyst preparation, specifically to a core-shell structured catalyst, its preparation method and application, and a method for synthesizing 1,3-propanediol from glycerol. Background Technology
[0002] In the production of biodiesel, glycerol is a major byproduct, accounting for approximately 10% of the total output. Utilizing this glycerol to synthesize high-value-added 1,3-propanediol has significant potential and importance. 1,3-Propanediol is an important monomer used to manufacture poly(1,3-propanediol terephthalate) (PTT), a material that combines the advantages of polyethylene terephthalate (PET) and polybutylene terephthalate (PET). PTT is widely used in the production of high-end polymeric products such as medical devices, premium carpets, and sportswear. The method of using glycerol to produce high-value-added compounds not only solves the problem of glycerol byproduct utilization but also provides a green, environmentally friendly, and sustainable approach to the production of high-end polymeric materials.
[0003] Traditional industrial production methods for 1,3-propanediol, such as Shell's ethylene oxide carbonylation hydrogenation method and Degussa and DuPont's acrolein hydration hydrogenation method, have been discontinued due to complex processes, harsh reaction conditions, and environmental pollution, leading to a supply shortage of 1,3-propanediol. Although DuPont (CN200380104657.2) disclosed a method for converting sugar sources into 1,3-propanediol through bio-fermentation, this requires the addition of expensive vitamin B12, resulting in high costs. Another method for converting glycerol into 1,3-propanediol through bio-fermentation (Appl. Microbiol. Biotechnol. 1992, 36, 592-597), while reported, suffers from low conversion efficiency due to the influence of biological metabolic activity, and the product contains impurities such as vitamins and salts, with extremely high separation energy consumption.
[0004] Based on the above problems, the direct hydrogenolysis of glycerol to produce 1,3-propanediol provides a more optimized method and pathway for high-value-added conversion and upgrading. However, current catalysts have two key problems: (1) The catalysts with better activity are mainly composed of W and Pt as the main active components, but in this reaction system, due to water as a solvent, Pt is prone to agglomeration and loss under hydrothermal reaction conditions, leading to catalyst deactivation. (2) The hydrogen spillover capacity is weak, and the activity is low. Therefore, how to improve both the activity and stability of the catalyst at the same time has become the main problem that needs to be solved. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of low activity and poor stability of existing catalysts for the synthesis of 1,3-propanediol in hydrothermal reactions, and to provide a core-shell structured catalyst, its preparation method and application, and a method for synthesizing 1,3-propanediol from glycerol. This catalyst has a TiO2 nanofilm shell supported on W, which can enhance hydrogen overflow and stabilize Pt nanoparticles in the interlayer, thus giving the catalyst high catalytic activity.
[0006] To achieve the above objectives, the first aspect of the present invention provides a core-shell structured catalyst, wherein the catalyst comprises a core, an interlayer, and a shell, the core of the catalyst comprises an inorganic oxide, the interlayer comprises Pt nanoparticles, and the shell comprises a W-containing TiO2 nanofilm.
[0007] The inorganic oxide is selected from at least one of alumina, zirconium oxide and silicon dioxide.
[0008] Preferably, the average particle size of the kernel is 0.1-10 μm, more preferably 0.2-2 μm.
[0009] Preferably, the average particle size of the Pt nanoparticles in the interlayer is 0.5-6 nm, and more preferably 2-4 nm.
[0010] Preferably, the Pt nanoparticles have a mass percentage content of 0.2-4 wt%, more preferably 1-2 wt%, based on the total mass of the catalyst.
[0011] Preferably, the thickness of the W-containing TiO2 nanofilm is 0.1-80 nm, and more preferably 5-50 nm.
[0012] Preferably, the W-containing TiO2 nanofilm has mesoporous structure.
[0013] Preferably, the mass percentage of W in the catalyst, based on the total mass of the catalyst and based on W oxide, is 0.5-10 wt%, more preferably 2-6 wt%.
[0014] A second aspect of the present invention provides a method for preparing a core-shell structured catalyst, wherein the method includes the following steps:
[0015] (1) Loading Pt nanoparticles onto inorganic oxides to obtain the first preproduct;
[0016] (2) The first preproduct is brought into contact with the interfacial assembly solution to carry out a synthesis reaction, and the second preproduct is obtained.
[0017] (3) Load W onto the second preproduct and calcine to obtain a core-shell structured catalyst;
[0018] The inorganic oxide is selected from at least one of alumina, zirconium oxide and silicon dioxide.
[0019] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0020] The fourth aspect of this invention provides the use of the catalyst described in the first or third aspect in the synthesis of 1,3-propanediol.
[0021] The fifth aspect of the present invention provides a method for synthesizing 1,3-propanediol from glycerol, wherein the method comprises: contacting glycerol and hydrogen in the presence of the catalyst described in the first or third aspect to carry out a hydrogenolysis reaction.
[0022] The beneficial effects achieved through the above technical solution are as follows:
[0023] (1) In this invention, the catalyst has a core-shell structure. The TiO2 nanofilm containing W in the outer shell plays a role in fixing the Pt nanoparticles in the interlayer, resulting in a more stable structure and avoiding the aggregation and loss of active components. The W loaded in the outer shell can also provide more catalytic active sites. The catalyst has high activity and high hydrothermal stability.
[0024] (2) In this invention, preferably, the W-containing TiO2 nanofilm is a mesoporous nanofilm. Compared with conventional TiO2 nanoparticle-based films, mesoporous films have higher hydrogen mass transfer efficiency and are more likely to pass through the outer shell to reach the Pt active sites in the interlayer, thereby improving the activity of the catalyst. Attached Figure Description
[0025] Figure 1 This is a scanning electron microscope image of the core-shell structured catalyst prepared in Example 1;
[0026] Figure 2 This is a transmission electron microscope (TEM) image of the core-shell structured catalyst prepared in Example 1. Detailed Implementation
[0027] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0028] The first aspect of the present invention provides a core-shell structured catalyst, wherein the catalyst comprises a core, an interlayer, and a shell, the core of the catalyst comprises an inorganic oxide, the interlayer comprises Pt nanoparticles, and the shell comprises a W-containing TiO2 nanofilm.
[0029] The inorganic oxide is selected from at least one of alumina, zirconium oxide and silicon dioxide.
[0030] In this invention, the innermost layer of the core-shell catalyst is the core, the middle interlayer covers the core, and the interlayer is covered by the outermost shell. In this invention, the catalyst has a core-shell structure, and the W-containing TiO2 nanofilm in the shell helps to fix the Pt nanoparticles in the interlayer, resulting in a more stable structure and preventing the aggregation and loss of active components. The W supported on the shell also provides more catalytic active sites. Therefore, the catalyst exhibits high activity and high hydrothermal stability.
[0031] According to the present invention, preferably, the average particle size of the core of the catalyst is 0.1-10 μm, for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, 5 μm, 7 μm, 10 μm, or any range between the two, preferably 0.2-2 μm. The average particle size of the core refers to the average particle size of the core particles, which can be a single particle or a particle aggregate formed by the aggregation of several small particles.
[0032] In this invention, the use of the aforementioned inorganic oxide core can promote the uniform synthesis of TiO2 nanofilms on the surface of the core, thereby improving catalytic activity.
[0033] In this invention, the average particle size of the catalyst core is measured using scanning electron microscopy (SEM). The average value is obtained by randomly measuring the size of 100 core particles using NanoMeasurer software. During the measurement process, the size of a core particle is the straight-line distance connecting the two farthest endpoints of the particle in the electron micrograph. The average particle size has the conventional interpretation in the art, referring to the particle size; for spherical particles, it refers to the diameter of the sphere; for irregular particles, it refers to the largest straight-line distance within the particle.
[0034] According to the present invention, preferably, the average particle size of the Pt nanoparticles in the interlayer is 0.5-6 nm, for example, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 6 nm, or any range between the two, preferably 2-4 nm. In the present invention, the average particle size of the Pt nanoparticles is measured by transmission electron microscopy (TEM), and the average value is taken from the particle size of 100 randomly measured Pt nanoparticles in the TEM image.
[0035] In this invention, the average particle size of the Pt nanoparticles meets the above-mentioned range limit, the Pt nanoparticles have better loading stability, can be uniformly dispersed on the core surface, and improve the catalytic activity of the catalyst.
[0036] According to the present invention, preferably, the Pt nanoparticles have a mass percentage content of 0.2-4 wt% based on the total mass of the catalyst, for example, 0.2 wt%, 0.4 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, or any range between the two, preferably 1-2 wt%.
[0037] In this invention, the mass percentage of Pt nanoparticles and W oxides in the core-shell structured catalyst is obtained by ICP testing.
[0038] According to the present invention, preferably, the thickness of the W-containing TiO2 nanofilm is 0.1-80 nm, for example, 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or any range between the two, preferably 5-50 nm, more preferably 10-35 nm. This preferred embodiment is more conducive to forming a stable multilayer core-shell structure, fixing the Pt nanoparticles in the interlayer, improving the hydrothermal stability of the catalyst, increasing the active sites of W in the shell, and further improving the catalytic activity of the catalyst.
[0039] In this invention, the thickness of the W-containing TiO2 nanofilm is obtained by transmission electron microscopy. The thickness of the nanofilm at 30 random locations in the transmission electron microscope image is measured, and the average value is taken.
[0040] According to the present invention, preferably, the W-containing TiO2 nanofilm has mesoporous structure. In this invention, as can be seen from the scanning electron microscope image of the core-shell structured catalyst, the W-containing TiO2 nanofilm has an ordered mesoporous structure, which fixes the Pt nanoparticles, improves the stability of the catalyst, and prevents the aggregation and loss of active components. Compared with films composed of conventional TiO2 nanoparticles, it has higher mass transfer efficiency, and the raw materials can more easily pass through the shell and reach the active sites in the interlayer, resulting in higher catalytic activity.
[0041] According to the present invention, preferably, the average pore size of the W-containing TiO2 nanofilm is 2-12 nm, for example, 2 nm, 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, or any range between the two, preferably 6-10 nm. In the present invention, the average pore size of the W-containing TiO2 nanofilm is measured by a low-temperature nitrogen adsorption method.
[0042] According to the present invention, preferably, the mass percentage of W in the catalyst, based on the total mass of the catalyst and based on W oxide, is 0.5-10 wt%, for example, 0.5 wt%, 0.6 wt%, 0.8 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 9 wt%, 10 wt%, or any range between the two, preferably 2-6 wt%. In the present invention, the mass percentage of W in the catalyst satisfying the above range provides more active sites in the catalyst shell, thereby improving the catalytic activity of the catalyst.
[0043] A second aspect of the present invention provides a method for preparing a core-shell structured catalyst, wherein the method includes the following steps:
[0044] (1) Loading Pt nanoparticles onto inorganic oxides to obtain the first preproduct;
[0045] (2) The first preproduct is brought into contact with the interfacial assembly solution to carry out a synthesis reaction, and the second preproduct is obtained.
[0046] (3) Load W onto the second preproduct and calcine to obtain a core-shell structured catalyst;
[0047] The inorganic oxide is selected from at least one of alumina, zirconium oxide and silicon dioxide.
[0048] In this invention, preferably, Pt nanoparticles are loaded onto the core using the above method, and a TiO2 nanofilm containing W is further coated onto the outer shell to form a stable multilayer core-shell structure. The preparation method is simple and can flexibly adjust the loading amount of W in the outer layer and the Pt nanoparticles in the interlayer, as well as the thickness of the outer shell layer.
[0049] According to the present invention, the loading method is not particularly limited, and those skilled in the art can choose conventional loading methods. Preferably, the loading process in step (1) includes:
[0050] The inorganic oxide and the Pt-containing nanoparticle solution were ultrasonically mixed and dried to obtain the first preproduct.
[0051] In this invention, the source of the inorganic oxide is not particularly limited; it can be commercially available or prepared using existing methods. The size range of the inorganic oxide is relatively wide, as long as it meets the limitation on the average particle size of the core as specified in the foregoing description. Preferably, for example, the inorganic oxide with an average particle size meeting the limitation can be obtained by ball milling or grinding.
[0052] According to the present invention, preferably, the mass ratio of the inorganic oxide to the Pt nanoparticles is 1:0.002-0.04, for example 1:0.002, 1:0.004, 1:0.006, 1:0.008, 1:0.01, 1:0.02, 1:0.03, 1:0.04, or any range between the two, preferably 1:0.01-0.02.
[0053] In this invention, the conditions for ultrasonic mixing are not particularly limited, as long as the Pt nanoparticles are uniformly loaded on the surface of the inorganic oxide. The method of adding each substance during the loading process is not particularly limited; they can be added separately or together. Preferably, the ultrasonic mixing conditions include a mixing time of 2-6 hours.
[0054] According to a preferred embodiment of the present invention, the method further includes solid-liquid separation of the ultrasonic mixture and drying of the obtained solid product. Centrifugation is preferably used to obtain the solid product; the conditions for centrifugation are not particularly limited and can be adjusted by those skilled in the art based on the separation results.
[0055] According to the present invention, the drying conditions are not particularly limited. Preferably, the drying conditions include: a heating temperature of 40-120°C, more preferably 60-100°C; and a heating time of 1-15 hours, more preferably 3-10 hours.
[0056] According to the present invention, the source of the Pt-containing nanoparticle solution is not particularly limited. Preferably, the method for preparing the Pt-containing nanoparticle solution includes: mixing a Pt source, a first template agent, and a first solvent, and refluxing the mixture to obtain the Pt-containing nanoparticle solution.
[0057] According to the present invention, preferably, the amount of Pt source used is based on Pt element, and the mass ratio of Pt source: first template agent: first solvent is (1-5):(5-50):(500-10000), more preferably (2-4):(10-30):(1000-5000). Adding the above substances according to the above amounts enables the preparation of a Pt nanoparticle solution with a more uniform average particle size distribution.
[0058] According to the present invention, preferably, the reflux conditions include: a reflux temperature of 60-200°C, preferably 80-180°C, under a protective atmosphere; and a reflux time of 0.5-6 h, preferably 2-4 h. Reflux under these conditions yields Pt nanoparticles with a more uniform average particle size distribution and a stable Pt nanoparticle solution.
[0059] In this invention, the type of protective atmosphere is not particularly limited, but is preferably selected from at least one of argon, nitrogen and helium.
[0060] According to the present invention, the type of Pt source is not particularly limited, and can be a conventional platinum-containing compound that can provide Pt in the art. Preferably, the Pt source is selected from at least one of chloroplatinic acid, tetraammineplatinum nitrate and potassium chloroplatinate.
[0061] According to the present invention, preferably, the first template agent is selected from at least one of polyvinylpyrrolidone, polyethyleneimine and oleylamine.
[0062] According to the present invention, the type of the first solvent is not particularly limited. Preferably, the first solvent is selected from at least one of water, saturated monohydric alcohols having 1-3 carbon atoms, and saturated dihydric alcohols having 1-3 carbon atoms. The solvent is selected from at least one of methanol aqueous solution, ethanol aqueous solution, and propanol aqueous solution. More preferably, the solvent is water and ethanol. The volume ratio of water to alcohol is not particularly limited, but preferably the volume ratio of water to alcohol is 1:1-10.
[0063] According to the present invention, preferably, in step (2), the second preproduct is synthesized by a confined interface single-micromicelle assembly method. In the present invention, the catalyst shell formed after calcination of the second preproduct synthesized by the above method comprises an ordered mesoporous TiO2 nanofilm containing W, resulting in higher mass transfer efficiency and higher catalytic activity.
[0064] According to the present invention, preferably, the interface assembly solution comprises a second template agent, a first acid, a second acid, a titanium source, and a second solvent.
[0065] According to the present invention, preferably, in the interface assembly solution, the mass ratio of the second template agent: the first acid: the second acid: the titanium source: the second solvent is 1:(0.1-10):(0.1-10):(0.1-10):(1-100), more preferably 1:(1-3):(1-5):(0.5-7):(2-50).
[0066] According to the present invention, the type and source of the second template agent are not particularly limited, and it is a template agent conventionally used in confined interface single-micromicelle assembly methods. Preferably, the second template agent is selected from at least one of polyoxyethylene polyoxypropylene ether, polyoxyethylene-polyoxybutene ether, and polyoxyethylene-polyoxyethylene-polyoxypropylene.
[0067] According to the present invention, the type of titanium source is not particularly limited and can be a conventional titanium-containing compound. Preferably, the titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, and tetraoctyl titanate.
[0068] In this invention, preferably, the first acid is acetic acid and / or citric acid. The addition of the aforementioned weak organic acid provides a mild acidic environment for the interfacial assembly solution.
[0069] In this invention, preferably, the second acid is concentrated hydrochloric acid and / or concentrated nitric acid. In this invention, the addition of the aforementioned strong acid further adjusts the interfacial assembly solution to an acidic environment.
[0070] In this invention, preferably, the second solvent is selected from at least one of tetrahydrofuran, 2-methyltetrahydrofuran, and cyclopentyl methyl ether.
[0071] According to a preferred embodiment of the present invention, a second template agent, acetic acid, concentrated hydrochloric acid, titanium source and a second solvent are mixed, stirred thoroughly, and the second solvent is evaporated to obtain a template agent / TiO2 composite monomer micelle gel.
[0072] In this invention, preferably, the above-mentioned gel and tricresylbenzene are dispersed in a mixed solvent to form an interfacial assembly solution. The mixed solvent comprises anhydrous ethanol and glycerol. In this invention, the amount of tricresylbenzene and the mixed solvent used is not particularly limited, as long as a transparent interfacial assembly solution can be formed.
[0073] According to a preferred embodiment of the present invention, the above-mentioned gel and tricresylene are dispersed in anhydrous ethanol and stirred, and glycerol is added dropwise to form a transparent interface assembly solution.
[0074] According to a preferred embodiment of the present invention, the amount of trimethylbenzene used is 0.5-4 mL, based on 1 g of the template agent / TiO2 composite monomer micelle gel.
[0075] According to a preferred embodiment of the present invention, based on 1 g of the template agent / TiO2 composite monomer micelle gel, the amount of the mixed solvent used is 2-10 mL. The volume ratio of anhydrous ethanol to glycerol in the mixed solvent is 0.5-2:1.
[0076] In this invention, preferably, the interface assembly solution is mixed with anhydrous ethanol containing a W-containing bis-inorganic oxide loaded with Pt nanoparticles to carry out the synthesis reaction. The mass ratio of the interface assembly solution to the first preproduct is not particularly limited, such that the thickness of the TiO2 nanofilm of the catalyst shell is 0.1-80 nm, preferably 5-50 nm.
[0077] According to the present invention, preferably, the synthesis conditions include: a reaction temperature of 80-180℃, more preferably 100-160℃; and a reaction time of 2-12 h, more preferably 4-8 h. In the present invention, preferably, the synthesis reaction is carried out under stirring conditions. The stirring rate is not particularly limited, but is preferably 100-400 rpm.
[0078] In this invention, preferably, the method includes cooling the synthetic reaction product to room temperature and then centrifuging and drying it to obtain a second preproduct.
[0079] According to the present invention, preferably, the loading process in step (3) includes: contacting the second preproduct with the W source.
[0080] According to the present invention, the W source can be selected from a wide range of types, including W-containing compounds conventional in the art. Preferably, the W source is selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate.
[0081] According to the present invention, preferably, the amount of W source used is based on oxides, and the mass ratio of W source to the second preproduct is (0.5-10):(90-99.5), preferably (2-5):(95-98).
[0082] In this invention, the loading method is not particularly limited, and conventional loading methods in the art can be selected. For example, impregnation or coating methods can be used.
[0083] According to a preferred embodiment of the present invention, a solution containing a W source is coated onto the surface of a second preproduct and then dried.
[0084] According to the present invention, preferably, the calcination conditions include: a calcination temperature of 200-600℃, more preferably 300-500℃; and a calcination time of 1-10h, more preferably 3-6h. In the present invention, preferably, calcination removes the template agent and increases the crystallinity, thereby loading W onto the surface of the TiO2 nanofilm and improving the catalytic activity.
[0085] In this invention, preferably, the calcination is carried out under a protective atmosphere. The protective atmosphere is described in the foregoing specification.
[0086] A third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0087] The fourth aspect of this invention provides the use of the catalyst described in the first or third aspect in the synthesis of 1,3-propanediol.
[0088] The fifth aspect of the present invention provides a method for synthesizing 1,3-propanediol from glycerol, wherein the method comprises: contacting glycerol and hydrogen in the presence of the catalyst described in the first or third aspect to carry out a hydrogenolysis reaction.
[0089] In this invention, the above-mentioned catalyst is used to synthesize 1,3-propanediol from glycerol. The catalyst has high reactivity, high feed conversion rate, and high selectivity for the target product, which can meet the requirements of long-term operation.
[0090] According to the present invention, preferably, the conditions for the hydrogenolysis reaction include: a reaction temperature of 120-200°C, more preferably 130-170°C, and a hydrogen pressure of 1-6 MPa, more preferably 3-5 MPa;
[0091] And / or, the conditions for the hydrogenolysis reaction include: a reaction time of 4-500 h, preferably 8-360 h.
[0092] According to the present invention, preferably, the glycerol is added in the form of an aqueous glycerol solution, wherein the concentration of glycerol in the aqueous glycerol solution is 10-90 wt%, preferably 30-80 wt%.
[0093] According to the present invention, the apparatus for the reaction is not particularly limited; preferably, when the reaction is carried out in a fixed-bed reactor, the liquid hourly space velocity is 0.05-5 h⁻¹. -1 Preferably 0.1-2h -1 The liquid phase refers to an aqueous solution of glycerol.
[0094] The present invention will be described in detail below through examples and comparative examples. Unless otherwise specified, the reagents and materials used in the following examples and comparative examples are commercially available, and the room temperature is 25±5℃.
[0095] The polyoxyethylene polyoxypropylene ether (Pluronic F127) was purchased from Aladdin, product number A196247.
[0096] Example 1
[0097] (1) Take 100 mL of water and 100 mL of ethanol and place them in a 1 L round-bottom flask. Add 0.1 g of Pt and 0.6 g of polyvinylpyrrolidone (PVP) through 8 wt% chloroplatinic acid solution. Stir for 5 minutes, then heat to 100 °C and reflux for 3 hours under an argon atmosphere to obtain a Pt nanoparticle solution. Add 5 g of SiO2 core to 200 mL of the above Pt nanoparticle solution, stir under ultrasonic conditions for 3 hours, centrifuge, and dry at 80 °C for 6 hours to obtain the first preproduct SiO2@Pt with an average particle size of 0.3 μm.
[0098] (2) 1.5 g of the triblock copolymer polyoxyethylene-polyoxypropylene ether (Pluronic F127), 2.4 mL of acetic acid, 3.2 mL of concentrated hydrochloric acid, and 1 g of tetrabutyl titanate were gradually added to 30 mL of tetrahydrofuran. After vigorous stirring for 10 minutes, the mixture was placed in an oven at 45 °C and allowed to stand for 24 hours to slowly evaporate the tetrahydrofuran solvent. A white-yellow polyoxyethylene-polyoxypropylene ether / TiO2 composite monomer micelle gel was obtained. 3 g of the gel formed above and 3 mL of trimethylbenzene were redispersed in 10 mL of anhydrous ethanol and stirred for 10 minutes. Then, glycerol (10 mL) was added dropwise and stirred for 5 minutes to form a transparent solution. Then, anhydrous ethanol (2 mL) containing 1 g of the first preproduct was added to the mixture. The entire solution was heated to 100 °C in an oil bath and stirred gently (350 rpm) for 6 hours. After cooling to room temperature, the solution was centrifuged and dried to obtain the second preproduct SiO2@Pt@TiO2.
[0099] (3) Ammonium metatungstate was loaded onto the second preproduct SiO2@Pt@TiO2. The amount of ammonium metatungstate added was calculated as WO3. The mass ratio of WO3 to SiO2@Pt@TiO2 was 5:95. The average particle size of SiO2@Pt@TiO2 was 0.36 μm.
[0100] The second template agent was removed by calcination at 350°C for 3 hours under a nitrogen atmosphere to obtain the SiO2@Pt@W-TiO2 core-shell structure catalyst.
[0101] Figure 1 and Figure 2 The images are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the core-shell structured catalyst prepared in Example 1, respectively. Figure 1 It can be seen from this that the outer shell is composed of ordered mesopores. Figure 2 The average thickness of the W-containing TiO2 nanofilm was measured to be 33 nm.
[0102] Example 2
[0103] The catalyst was prepared according to the method of Example 1, except that SiO2 was replaced with an equal mass of ZrO2 in step (1), and other conditions were the same as in Example 1, to obtain ZrO2@Pt@W-TiO2 catalyst.
[0104] Example 3
[0105] The catalyst was prepared according to the method of Example 1, except that the amount of ammonium metatungstate added in step (3) was changed so that the mass ratio of WO3 to the second preproduct was 3:97. Other conditions were the same as in Example 1, and a SiO2@Pt@W-TiO2 core-shell structure catalyst was obtained.
[0106] Example 4
[0107] (1) Take 20 mL of water and 180 mL of propanol and place them in a 500 mL round bottom flask. Add 0.2 g of Pt and 0.6 g of polyvinylpyrrolidone (PVP) through tetraammineplatinum nitrate (Pt source). Stir for 5 minutes, then heat to 90 °C and reflux for 3 hours under an argon atmosphere to obtain a Pt nanoparticle solution.
[0108] 10g of alumina core (average particle size of 0.3μm) was added to 100mL of the above Pt nanoparticle solution, stirred under ultrasonic conditions for 3 hours, centrifuged, and then heated at 80℃ for 5 hours to obtain the first preproduct Al2O3@Pt.
[0109] (2) 1.8 g of the triblock copolymer polyoxyethylene-polyoxybutylene ether, 2.6 mL of acetic acid, 3.0 mL of concentrated hydrochloric acid, and 1.38 g of tetrabutyl titanate were gradually added to 30 mL of tetrahydrofuran. After vigorous stirring for 10 minutes, the mixture was placed in an oven at 45 °C and allowed to stand for 24 hours to slowly evaporate the tetrahydrofuran solvent. A white-yellow polyoxyethylene-polyoxypropylene ether / TiO2 composite monomer micelle gel was obtained. 3 g of the gel formed above and 3 mL of trimethylbenzene were redispersed in 10 mL of anhydrous ethanol and stirred for 10 minutes. Then, glycerol (10 mL) was added dropwise and stirred for 5 minutes to form a transparent solution. Then, anhydrous ethanol (2 mL) containing 1 g of the second preproduct was added to the mixture. The entire solution was heated to 95 °C in an oil bath and stirred gently (350 rpm) for 8 hours. After cooling to room temperature, the solution was centrifuged and dried to obtain the second preproduct Al2O3@Pt@TiO2.
[0110] (3) Ammonium paratungstate was loaded onto the second preproduct. The amount of ammonium paratungstate added was based on WO3. The mass ratio of WO3 to the second preproduct was 4:96. The average particle size of Al2O3@Pt@TiO2 was 0.4 μm.
[0111] The second template agent was removed by calcination at 450°C for 4 hours under a nitrogen atmosphere to obtain the Al2O3@Pt@W-TiO2 core-shell structure catalyst.
[0112] Example 5
[0113] The catalyst was prepared according to the method of Example 1, except that in step (3), the amount of ammonium metatungstate added was changed so that the mass ratio of WO3 to the second preproduct was 1:9, and other conditions were the same as in Example 1, and a core-shell structure catalyst was obtained.
[0114] Example 6
[0115] The catalyst was prepared according to the method of Example 1, except that the amount of titanium source added in step (3) was changed so that the thickness of the TiO2 nanofilm was 65 nm. Other conditions were the same as in Example 1, and a core-shell structure catalyst was obtained.
[0116] Comparative Example 1
[0117] The catalyst was prepared according to the method of Example 1, except that step (2) was omitted, and W was directly loaded onto the first preproduct of step (1), followed by centrifugation, drying, and calcination. Other conditions were the same as in Example 1 to obtain the catalyst.
[0118] Comparative Example 2
[0119] The catalyst was prepared according to the method of Example 1, except that tetrabutyl titanate was not added in step (2), and the other conditions were the same as in Example 1. TiO2 nanofilm could not be formed.
[0120] Comparative Example 3
[0121] The catalyst was prepared according to the method of Example 1, except that W was not loaded in step (3), and the second preproduct was directly calcined to obtain a core-shell structure catalyst.
[0122] Test case
[0123] The structural parameters and active component contents of the catalysts prepared in the examples and comparative examples are shown in Table 1.
[0124] Table 1
[0125]
[0126] Weigh 1g of the catalyst obtained in the examples and comparative examples, place it in a fixed-bed reactor, and react it at a temperature of 160°C and a hydrogen pressure of 4MPa. The mass hourly space velocity (WHSV) of the glycerol aqueous solution is 1h. -1 A 60wt% aqueous glycerol solution was introduced, and the liquid from the outlet was collected after 8 hours and 360 hours of reaction and analyzed by gas chromatography. The results are shown in Table 2.
[0127] Table 2
[0128]
[0129]
[0130] As can be seen from Table 1, the Pt content of the multi-layer core-shell structure catalyst remained almost unchanged before and after the reaction, while the Pt content of the comparative catalyst without shell protection decreased by 8 wt% after 360 h of reaction.
[0131] As can be seen from the results in Table 2, the catalyst prepared using the embodiments of the present invention, when used for the hydrogenolysis of glycerol to 1,3-propanediol, exhibits higher hydrothermal stability compared to catalysts synthesized by existing methods. It can suppress the loss and aggregation of Pt, and significantly improves the glycerol conversion rate and the selectivity of 1,3-propanediol in the product. Furthermore, after 360 hours of operation, the activity of the multilayer core-shell structure catalyst only slightly decreased, while the activity of the catalyst without a shell decreased by 50%, indicating that the multilayer core-shell structure catalyst has excellent stability.
[0132] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A core-shell structured catalyst, characterized in that, The catalyst comprises a core, a sandwich layer, and a shell. The core of the catalyst comprises an inorganic oxide, the sandwich layer comprises Pt nanoparticles, and the shell comprises a TiO2 nanofilm containing W. The inorganic oxide is selected from at least one of alumina, zirconium oxide and silicon dioxide.
2. The catalyst according to claim 1, wherein, The average particle size of the kernel is 0.1-10 μm, preferably 0.2-2 μm; Preferably, the average particle size of the Pt nanoparticles in the interlayer is 0.5-6 nm, more preferably 2-4 nm; Preferably, the Pt nanoparticles have a mass percentage content of 0.2-4 wt%, more preferably 1-2 wt%, based on the total mass of the catalyst.
3. The catalyst according to claim 1 or 2, wherein, The thickness of the W-containing TiO2 nanofilm is 0.1-80 nm, preferably 5-50 nm; Preferably, the W-containing TiO2 nanofilm has mesoporous structure; Preferably, the mass percentage of W in the catalyst, based on the total mass of the catalyst and based on W oxide, is 0.5-10 wt%, more preferably 2-6 wt%.
4. A method for preparing a core-shell structured catalyst, characterized in that, The method includes the following steps: (1) Loading Pt nanoparticles onto inorganic oxides to obtain the first preproduct; (2) The first preproduct is brought into contact with the interfacial assembly solution to carry out a synthesis reaction, and the second preproduct is obtained. (3) Load W onto the second preproduct and calcine to obtain a core-shell structured catalyst; The inorganic oxide is selected from at least one of alumina, zirconium oxide and silicon dioxide.
5. The preparation method according to claim 4, wherein, The load process described in step (1) includes: The inorganic oxide and the Pt nanoparticle-containing solution were ultrasonically mixed and dried to obtain the first preproduct. Preferably, the mass ratio of the inorganic oxide to the Pt nanoparticles is 1:0.002-0.04, and more preferably 1:0.01-0.
02.
6. The method according to claim 5, wherein, The method for preparing the Pt-containing nanoparticle solution includes: mixing a Pt source, a first template agent, and a first solvent, and then refluxing the mixture to obtain a Pt-containing nanoparticle solution. Preferably, the amount of Pt source used is calculated based on Pt element, and the mass ratio of Pt source: first template agent: first solvent is (1-5):(5-50):(500-10000), preferably (2-4):(10-30):(1000-5000); Preferably, the reflux conditions include: under a protective atmosphere, a reflux temperature of 60-200℃, preferably 80-180℃; and a reflux time of 0.5-6h, preferably 2-4h. Preferably, the Pt source is selected from at least one of chloroplatinic acid, tetraammineplatinum nitrate, and potassium chloroplatinate.
7. The method according to any one of claims 4-6, wherein, In step (2), the second preproduct is synthesized by a confined interface single micromicelle assembly method; Preferably, the interface assembly solution comprises a second template agent, a first acid, a second acid, a titanium source, and a second solvent; Preferably, the synthesis conditions include: a reaction temperature of 80-180℃, more preferably 100-160℃; and a reaction time of 2-12h, more preferably 4-8h.
8. The method according to claim 7, wherein, In the interface assembly solution, the mass ratio of the second template agent: the first acid: the second acid: the titanium source: the second solvent is 1:(0.1-10):(0.1-10):(0.1-10):(1-100), preferably 1:(1-3):(1-5):(0.5-7):(2-50); Preferably, the second template agent is selected from at least one of polyoxyethylene polyoxypropylene ether, polyoxyethylene-polyoxybutylene ether, and polyoxyethylene-polyoxypropylene. Preferably, the titanium source is selected from at least one of tetrabutyl titanate, tetraethyl titanate, and tetraoctyl titanate.
9. The method according to any one of claims 4-8, wherein, The loading process described in step (3) includes: contacting the second preproduct with the W source; Preferably, the W source is selected from at least one of ammonium metatungstate, ammonium paratungstate, and sodium tungstate; Preferably, the amount of W source used is based on oxides, and the mass ratio of W source to the second preproduct is (0.5-10):(90-99.5), preferably (2-5):(95-98); Preferably, the calcination conditions include: a calcination temperature of 200-600℃, more preferably 300-500℃; and a calcination time of 1-10h, more preferably 3-6h.
10. The catalyst prepared by the method according to any one of claims 4-9.
11. The use of the catalyst according to any one of claims 1-3 and 10 in the synthesis of 1,3-propanediol.
12. A method for synthesizing 1,3-propanediol from glycerol, characterized in that, The method comprises: contacting glycerol and hydrogen in the presence of the catalyst described in any one of claims 1-3 and 10 to carry out a hydrogenolysis reaction; Preferably, the conditions for the hydrogenolysis reaction include: a reaction temperature of 120-200℃, more preferably 130-170℃, and a hydrogen pressure of 1-6MPa, more preferably 3-5MPa; And / or, the conditions for the hydrogenolysis reaction include: a reaction time of 4-500 h, preferably 8-360 h; Preferably, the glycerol is added in the form of an aqueous glycerol solution, wherein the concentration of glycerol in the aqueous glycerol solution is 10-90 wt%, preferably 30-80 wt%. Preferably, when the reaction is carried out in a fixed-bed reactor, the liquid hourly space velocity (LHSV) is 0.05-5 h⁻¹. -1 Preferably 0.1-2h -1 .
Citation Information
Patent Citations
Process for the biological production of 1,3-propanediol with high yield
CN100471946C
